Observation of a Lunar Eclipse at 89, 150, and 183 GHz - Martin J. Burgdorf; Niutao Liu; Stefan A. Buehler; Ya-Qiu Jin (The Planetary Science Journal, 2023)
We describe the measurement of the brightness temperature of the Moon from space during a total lunar eclipse by using a microwave sounder aboard a weather satellite. Previous observations of lunar eclipses were inconsistent and did not cover the frequency range between 100 and 200 GHz. In this work, we seek to establish a reliable relationship between frequency and drop in brightness temperature during a total eclipse for millimeter wavelengths. For this purpose, we chose the eclipse on 2004 October 28, because it coincided with appearances of the Moon in the deep space view of the Advanced Microwave Sounding Unit-B on NOAA-15. It was therefore possible to measure its disk-integrated radiance at 89, 150, and 183 GHz at 100 minutes intervals. Our observations are, to the best of our knowledge, the only ones between 100 and 200 GHz, and demonstrate the nearly linear dependency on frequency of the maximum relative drop in effective temperature during an eclipse. The slope of this function is m = 0.00114 ± 0.00017 GHz ^−1 in the range 88–300 GHz. The good agreement between the variations of the effective lunar temperature and a new radiative-transfer model suggests that the Moon is suitable as a flux standard for microwave observations with beam sizes larger than 0.5°.